Komunikasi Penyandang Disabilitas di Loka Rehabilitasi Sosial Penyandang Disabilitas Sensorik Rungu Wicara (LRSPDSRW) â€œMeohaiâ€ Kendari - Ridwa, Fatmawati; Umran, La Ode Muh.; Jaya, Asrul (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2019)
The purpose of this research is to know and to describe how the types and processes of communication of person with disabilities in social rehabilitation venues for person with hearing impaired sensory disabilities Meohai Kendari . This research uses the Theory of Symbols by Littlejohn and the research method used in this research is a Qualitative research method with the subject of this research that is the employee / staff in the Social Rehabilitation venues for persons with hearing impaired sensory disabilities Meohai Kendari with informants totaling 7 people. The technique for determining informants in this research is the purposive sampling technique. While the data collection techniques used are observation, interviews, and documentation. The result of this research at the social rehabilitation venues for person with hearing impaired sensory disabilities Meohai Kendari showed that there were four (4) things related to the type of communication namely first; sign language of persons with disabilities, second; approach, third; paralanguage / vocals, and fourth; communication media. Whereas in the communication process that occurs there are three (3) things namely first; communication between persons with disabilities, second; communication between persons with disabilities and social workers, and third; communication of persons with disabilities and newcomer.